Sustainable livestock development in low and middle income countries – shedding light on evidence-based solutions: systematic literature search and expert survey - Paul, Birthe K.; Butterbach-Bahl, Klaus; Notenbaert, An Maria Omer; Nderi, Alex N.; Ericksen, Polly J. (Bioversity International and the International Center for Tropical Agriculture, 2020)
This dataset consists of two types of data that were used in the analysis for the perspective paper ‘Sustainable livestock development in low and middle income countries – shedding light on evidence-based solutions’: i) a sub-set of results of a systematic literature search in the Web of Science to take stock of the global distribution of research on livestock and the environment; ii) responses to four questions of an expert survey conducted among 260 respondents to explore global perceptions of environmental impacts of livestock and available solutions.